Analisis Perhitungan Overall Equipment Effectiveness (Oee) pada Mesin Rolling Stand 3 (Section Mill) - Rahmita, Ika; Cahyadi, Dadi; Winarno, Heru (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2016)
The problem that occurs at this time is that the production process is often hampered and does not reach the set targets because the Rolling Stand 3 (mill section) machines are often damaged. Rolling Stand 3 machine (section mill) is used to form steel with a grinding process (rolling). The study was conducted using the Overall Equipment Effectiveness (OEE) method where Overall Equipment Effectiveness (OEE) is a systematic method for measuring the level of machine effectiveness. Overall Equipment Effectiveness (OEE) calculations can be gauged from actual data related to Availability, Performance Rate, and Quality Rate. Overall Equipment Effectiveness (OEE) is used as an indicator, to find out the causes of machine ineffectiveness done by calculating Six Big Losses to find out what factors influence the Six Big Losses. Based on the research results for the period January - December 2015 on Rolling Stand 3 (mill section) machines, the Availability value was 55.77%, Performance Rate 60.05%, Quality Rate 97.82% and Overall Equipment Effectiveness (OEE) was 32.86 %, meaning Overall Equipment Effectiveness (OEE) below the standard value for world-class, which is 85%. To maximize overall machine effectiveness, improvements are needed to the factors that influence the low amount of Overall Equipment Effectiveness (OEE). When viewed from the six elements Six Big Losses, the greatest value is found in the Equipment Failure factor.